IMPROVING STUDENTS’ DESCRIPTIVE WRITING SKILLS THROUGH THE GENRE-BASED WRITING APPROACH - Jusnaini Hasni; Ana Elvia Jakfar; Lijah Adena Hasibuan (Universitas Bina Bangsa Getsempena, 2025)
All university students are required to have adequate English writing skills. This is true, particularly for students in Agro-Marine field, because they are expected to write and present scientific information in a structured and accurate manner. However, a number of students have challenges relating to English writing skill. This research aimed to investigate the implementation of Genre-Based Writing (GBW) in improving the descriptive writing skills of Agro-Marine students at Teuku Umar University. Fifty participants from the faculties of Agriculture, Fisheries, and Marine Sciences took part in the study. The method used in this study was descriptive approach. The data were collected from the participants’ writing tests for the pre-test and post-test, as for the assessment, a rubric consist of content, organization, vocabulary, grammar and mechanics. The researchers also conducted a semi-structured interviews and observations before, during and after the implementation of the genre-based writing. The data was examined by using descriptive qualitative framework proposed by Miles and Huberman (1994) which divided the process into three steps such as data reduction, data display and conclusion drawing. The result showed that participants’ text structure, coherence, and linguistic precision improved from 50 to 76,25 after the implementation of the genre-based writing. The results suggest that GBW is an effective pedagogical approach for enhancing Agro-Marine students’ writing skills.